2006
DOI: 10.1039/b600932h
|View full text |Cite
|
Sign up to set email alerts
|

A molecular tool kit for the variable design of logic operations (NOR, INH, EnNOR)

Abstract: A simple set of five components was used to design molecular logic gates based on phthalimide-sensitised Tb(III) luminescence, including the first report of an enabled NOR (EnNOR) gate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
53
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 34 publications
1
53
0
Order By: Relevance
“…Supramolecular structures have also been considered as switchable devices for logic operations. [103] Chemical-computing equivalents of standard binary gates, such as AND, [104,105] OR, [106] XOR, [103,107] NOR, [91,93,[108][109][110][111] NAND, [111][112][113] INHIB, [114][115][116][117] XNOR [118,119] have been realized.…”
Section: Introductionmentioning
confidence: 99%
“…Supramolecular structures have also been considered as switchable devices for logic operations. [103] Chemical-computing equivalents of standard binary gates, such as AND, [104,105] OR, [106] XOR, [103,107] NOR, [91,93,[108][109][110][111] NAND, [111][112][113] INHIB, [114][115][116][117] XNOR [118,119] have been realized.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10] In parallel, several groups have shown that it is possible realize complex combinational logic circuits at the molecular scale, up to half and full addition or subtraction using various external perturbations, i.e., chemical, biochemical, photochemical, optical, electrochemical, electrical, to address the system, encode the inputs and perform the logic operations. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] We propose here another approach for implementing molecular logic gates.…”
Section: Introductionmentioning
confidence: 99%
“…Then, the chemical processes could be programmed similar to computer programming [14,15], yielding networks performing several logic operations. Despite the fact that chemical systems based on organic molecules [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] or biomolecules [9,10], [32][33][34][35][36][37][38][39][40][41] achieved significant success in the formulation of single logic operations, and their short sequences mimicking natural biochemical pathways were successfully designed [42,43], there is no clear opinion about their possible applications. The present complexity of the chemical information processing systems is far below that of electronic computers and the timescale of their operation (minutes to hours) is too long to be competitive with electronics.…”
Section: Introductionmentioning
confidence: 99%
“…Application of highly sensitive techniques requires electronic transduction and amplification of the output signals produced by enzyme logic systems. This approach was actually applied to most chemical computing systems based on nonbiological molecules [1][2][3][4][5][6][7][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. While most nonbiochemical computing systems are based on the application of noncatalytic reactions, enzyme logic systems have the advantage of catalyzing biochemical transformations when continuous production of the output species could potentially produce substantial chemical changes in the systems even when the concentrations of the reacting catalytic species are low.…”
Section: Introductionmentioning
confidence: 99%